Ratio of coral reefs to macroalgae: An ecosystem approach management - Aditiyawan Ahmad; Achmad Fahrudin; Mennofatria Boer; Yusli Wardiatno; Mohammad Mukhlis Kamal (Depik, 2019)
Abstract. The decline in the quality of coral reef ecosystems is not only caused by human activities but also caused by competition in ecosystems, including competition for space and nutrients. Research on the comparison of coral reefs with macroalgae is one of the determinants of coral reef health which is the basis for the management of coral reefs with an ecosystem approach. The purpose of this study was to analyze the comparison of coral reef cover with macroalgae. The research method used is Line Intercept Transect (LIT), the research location is 13 stations divided into 3 locations, namely north, centre, and south from Ternate Island in North Maluku. The results showed that the condition of coral reefs ranged from 24 – 86.60%, based on the condition categories of 13 observation locations, the coral reefs of Ternate Island were in very good condition at 15.38%, good conditions at 46.16%, adequate conditions at 30.77%, and damaged conditions 7.69%, while the condition of macroalgae cover ranged from 0 - 30.60% in the area of coral reef ecosystems. The ratio of the of coral reefs to algae ranges from 0 to 1.117, based on the ratio value, it is classified as low, medium to high, spread in the coral reef ecosystem of Ternate Island. Coral reef management strategies on Ternate Island include a continuous monitoring program for coral reef ecosystems, education on coral reef ecosystems, creating a conscious community of waste, and limiting the capture and restoking of herbivorous fish in coral reef areas.Keywords: Coral reef, ecosystem approach management, macroalgae, Ternate Island